Protocol for potato propagative material production in liquid medium - Scherwinski Pereira, Jonny Everson; de Luces Fortes, Gerson Renan (Pesquisa Agropecuaria Brasileira, 2003)
Semi-solid media are more commonly used in studies of micropropagation, but the physical state of the culture media seems to influence the growth and multiplication rate of the cultivation. The objective of this work was to establish a protocol for in vitro multiplication of potato in liquid culture media. Potato explants, cultivar Eliza, with an axillary bud, were cultivated in six different culture media, with (semi-solid) or without (liquid) the addition of agar. After 21 days, the culture medium that provided the best results for growth and multiplication rate had the composition modified with the objective of improving the efficiency of in vitro multiplication of five cultivars in liquid medium. The need of agitation was also evaluated in liquid culture medium. There was high efficiency of the in vitro potato multiplication when it was cultivated in liquid medium. The MS salt medium in the full concentration, added by gibberellic acid (0.25 mg de Luces Fortes), panthotenic acid (5.0 mg L-1), thiamine (1.0 mg L-1) and sucrose (20 g L-1), and under constant agitation, showed to be suitable for this purpose.